Here I copy the steps and indicate where the error is.
Square root of negative 2x plus 1 − 3 = x=> <span>this is the starting equation
</span>
√[ - 2x + 1] - 3 = x
Square root of negative 2x plus 1 − 3 + 3 = x + 3 in this step she added 3 to each side, which is fine
<span> Square root
of negative 2x plus 1 = x + 3 <span>she made the addtions => fine</span></span>
Square root of negative 2x plus 1 − 1 = x + 3 – 1 due to <span>plus 1 in inside the square root, this step will not help</span>
<span> Square root
of negative 2 x = x + 2 <span>wrong! she cannot simplify - 1 that is out of the square root with +1 that is inside the square root
</span></span>
<span>Then, from here on all is wrong, but she made other additional mistakes.</span>
(Square root of negative 2 x)2 = (x − 4)2 −2x <span> the right side should be (x+2)^2 which is x^2 + 4x +4 not (x-4)^2 - 2x</span>
Later she made a mistake changing the sign of -8x to +8x
Those are the mistakes. Finally, the global error is that she should verify whether the found values satisfied the original equation.
Leah is baking a cake. The cake needs 1 2/8 of flour and 4 6/8 of sugar. Add the ingredients together. The answer is 4
The amswer would be 8.5 due to the length of the obeject
Answer:
Commission: $3625.70
Total (sales + commission): $59405.70
Step-by-step explanation:
6.5% of 55780 = 0.065 × 55780 = 3625.7
55780 increase 6.5% =
55780 × (1 + 6.5%) = 55780 × (1 + 0.065) = 59405.7